Pengaruh Pemberian Minuman Jahe Hangat Terhadap Tingkat Mual Pada Pasien Kanker Nasofaring Dengan Kemoterapi Di Ruang Teratai RSU Dr. Soetomo Surabaya Penelitian Quasy – Experimental - Endang Yulianingsih, - (2012)
Chemotherapy was a medical treatment that used anti-cancer drugs to systemically cancer, that can cause side effect of chemotherapy. The greatest side effect was nausea. Altough anti emetics have got by the patient, but in fact >80% of chemotherapy case get nausea even vomiting. Effort to overcome nausea safely and naturally can be done by giving a warm ginger. Ginger shown to reduce nausea related to chemotherapy side effect because the content of volatile substances in ginger works to supressing serotonin. This study was aims to explain the effect of giving a warm ginger drinks on the level of nausea in patients with nasopharyngeal cancer with chemotherapy in lotus room Dr.Soetomo Hospital Surabaya. This study used quasy experimental design with pre-post test control by revealing a causal relations between the treatment and control groups. Determination of sample using inclusion and exclusion criteria with purposive sampling technique. The independent variables was the provision of hot ginger while the dependent variable was the level of nausea. Data was collect used measure the nausea level with interview sheets based on severity of nausea National Cancer Institute (2006). The result of statistical with Wilcoxon Sign Rank test showed that value p=0,007. This proves that there was a significant effect on provision of hot ginger drinks for nausea of nasopharyngeal cancer patient with chemotherapy. Suggestions for the next researcher to observe both the macroscopic and microscopic about the most effective type of ginger to treat nausea.